2018
DOI: 10.1590/s0100-83582018360100040
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Productivity and Seed Nutrition of Cotton by Plant Growth Regulation under Deficient and Adequate Boron Conditions

Abstract: -Plant growth regulators (PGRs) potentially improve the productivity and nutritional quality of crops through modulation of morphology, physiology and nutrient dynamics within plants. However, the effect of PGRs may differ under environments with deficient and adequate nutrients. Here the role of mepiquat chloride (MC) on the yield and seed nutritional quality of cotton was explored under boron (B) deficiency and adequate conditions in a two-year field study. Mepiquat chloride was foliar-applied at different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…The increment in oil yield due to applying growth regulators could be attributed to their roles in increasing cotton seed yield /fed and oil percentage in the seeds. In this respect, oil yield/ha was found to be increased by spraying MC at rate of 70 mg/L in comparison with control treatment as previously reported by Zohaib et al (2018).…”
Section: -Yield and Seed Qualitysupporting
confidence: 81%
See 2 more Smart Citations
“…The increment in oil yield due to applying growth regulators could be attributed to their roles in increasing cotton seed yield /fed and oil percentage in the seeds. In this respect, oil yield/ha was found to be increased by spraying MC at rate of 70 mg/L in comparison with control treatment as previously reported by Zohaib et al (2018).…”
Section: -Yield and Seed Qualitysupporting
confidence: 81%
“…Application of MC + NAA caused an increase in the protein yield/fed amounted to 33.76 and 37.60% more than the untreated plants in the first and second seasons, respectively. In this concern, Zohaib et al (2018) found that application of 70 mg MC /L increased protein yield/ha compared to untreated plants.…”
Section: -Yield and Seed Qualitymentioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that ZnSO 4 could improve the growth, nutritional quality, and productivity of Washington navel orange trees [ 35 ]. Recent research has demonstrated that the use of mepiquat chloride (MC) can significantly boost the nutrient content and biological accumulation in seeds under the control circumstances of boron deficiency and sufficient boron, boosting the yield and nutritional quality of seed cotton [ 36 ]. Additionally, the productivity and quality of tomatoes can be increased by combining biochar with both organic and inorganic fertilizers [ 37 ].…”
Section: Factors Influencing the Nutritive Value Of Farm Commoditiesmentioning
confidence: 99%